On infinite horizon active fault diagnosis for a class of non-linear non-Gaussian systems - Punčochář, Ivo; Šimandl, Miroslav (Zielona Góra: Uniwersytet Zielonogórski)
The paper considers the problem of active fault diagnosis for discrete-time stochastic systems over an infinite time horizon. It is assumed that the switching between a fault-free and finitely many faulty conditions can be modelled by a finite-state Markov chain and the continuous dynamics of the observed system can be described for the fault-free and each faulty condition by non-linear non-Gaussian models with a fully observed continuous state.
Keywords: active fault detection; non-linear stochastic systems; optimal input design; dynamic programming